Impact of postoperative physical activity on the development of pneumonia in the subacute phase after esophagectomy in patients with esophageal cancer: A retrospective cohort study. (February 2023) - Kondo, Shin; Inoue, Tatsuro; Saito, Takashi; Fujikawa, Takashi; Kamada, Motomu; Inoue, Seiya; Fujiwara, Satoshi; Goto, Masakazu; Sato, Nori; Ono, Rei; Akisue, Toshihiro; Katoh, Shinsuke; et al.
Abstract: Purpose: Physical activity is important to improve recovery following surgery. This study investigated the impact of physical activity on the development of pneumonia after radical esophagectomy in patients with thoracic esophageal cancer in the subacute phase from postoperative day 11 to hospital discharge. Methods: This retrospective cohort study included 83 patients who underwent radical esophagectomy for esophageal cancer between 2016 and 2022. Physical activity was measured using an activity tracker, and the average number of steps between postoperative days 8 and 10 was examined. The primary outcome was pneumonia (Clavien-Dindo classification 2 or higher) developing between postoperative day 11 and hospital discharge. We used the receiver operating characteristic (ROC) curve analysis to calculate the optimal cutoff value of physical activity that can predict the development of pneumonia and define low physical activity. We used logistic regression analysis to investigate the impact of low physical activity on postoperative pneumonia. Results: Pneumonia developed in 10 patients (12.0%) during the observation period. The optimal cutoff value of physical activity for predicting pneumonia was 1494 steps per day (sensitivity: 60.0%, specificity: 89.0%, area under the curve: 0.743). In multivariate analysis, low physical activity was an independent predictor of incident pneumonia [odds ratio: 12.10, 95% confidence interval: 2.21–65.90, p = 0.004], with adjustment for age, gastric tube reconstruction route, and postoperative recurrent nerve palsy. Conclusions: Physical activity following radical esophagectomy in patients with thoracic esophageal cancer was an independent predictor of the development of pneumonia in the subacute phase after radical esophagectomy. Highlights: Postoperative pneumonia is a common complication of esophagectomy. This study examined the impact of physical activity on postoperative pneumonia. Walking less than 1494 steps per day post-surgery was a predictor of pneumonia. Promoting physical activity such as walking may prevent postoperative pneumonia.